The "seeing place": Teaching nurse practitioners about cultural difference through dramatization. (February 2021) - Vandermause, Roxanne; Fish, Anne F.; Bender, Annah; Kuensting, Laura; Murphy, Natalie; Lavin, Roberta
Abstract: Background: The use of dramatization in health professional education is one method to teach students about implicit bias and cultural difference, yet it has not been widely studied among graduate students of nursing. Objectives: The purpose of this article is to present a qualitative analysis of data regarding doctoral nursing students' responses to a new dramatic exercise as part of a funded project to facilitate cultural learning in a diversity-enhanced nursing curriculum. Design: We employed a cross-sectional posttest design with qualitative data collection and hermeneutic analysis. Setting and. Participants: Subjects were students from two cohorts in a Doctor of Nursing Practice program at a large metropolitan university in the Midwestern United States (n = 136). Methods: Following a dramatic exercise facilitated by a local theatre group, students debriefed and provided feedback via paper-based surveys collected by their instructor. The research team reviewed and analyzed student feedback with an eye toward new learning or insights around cultural difference. Results: Students rated the dramatic exercise highly. Their written feedback provided for a deeper exploration of how they internalized messages about cultural difference. These experiences were thematized in the following way: (a) Awareness is facilitated through integrating nonverbal (kinesthetic) and verbal encounters, (b) Hesitancy to participate in unfamiliar activities creates tension, and (c) Safety is a foundational aspect of learning sensitive issues. Conclusion: Dramatization of culturally sensitive scenarios for advanced practice nurses can lead to new understanding. Educators who understand the need for thoughtful introduction of dramatization experiences can better prepare nurses for interaction in cross-cultural clinical environments.